A review of microcredentials in health professions continuing professional development - Womack-Adams, Kelly; Morbitzer, Kathryn A.; Ondek, Christine; Collins, Heidi; McLaughlin, Jacqueline E. (Frontiers in Medicine, 2025)
Microcredentials are an emergent tool to support knowledge and skill development. Despite their growing popularity in medical education – and higher education more broadly – it is unclear how these strategies have been utilized to support continuing professional development in the health professions. A rapid systematic review was conducted to explore the current relevant literature due to the timely and evolving nature of microcredentials. PubMed, Embase, and ERIC were used for the article search. Of the 290 relevant articles found from the searches, a total of 11 articles were included after abstract and full-text screenings. All articles used in this review were published within the past 10 years. Microcredentials were used across various professions, covered a wide range of topics, and employed various teaching strategies. The definitions used for key terms like microcredential were inconsistent across articles.